Pengaruh Kompetensi Soft Skill Pustakawan Terhadap Kepuasan Pemustaka Di Perpustakaan FKIP UHAMKA - Wenny, Lili Sudria; Fadiah, Nanda; Lolytasari, Lolytasari (IQRA`: Jurnal Perpustakaan dan Informasi, 2024)
This research aims to Find out the level of soft skill competency of librarians in the FKIP UHAMKA Library, Find out how high the level of user satisfaction is in the FKIP UHAMKA Library, Find out the influence of librarian soft skill competency on user satisfaction in the FKIP Library UHAMKA simultaneously, and knowing the influence of librarian soft skills competency on user satisfaction at the FKIP UHAMKA Library partially. This research uses a quantitative approach with an associative type of research. The population in this study was all members of the FKIP UHAMKA library, totaling 5,602 people. Sampling was conducted using an accidental sampling technique with 100 respondents determined by calculating the Slovin formula. The primary data collection technique is a Likert scale questionnaire with four alternative answers. Meanwhile, supporting data collection techniques use interviews. The theory used in this research is Contrast Theory, which assumes that if the product performance perceived by consumers exceeds expectations, consumers will feel very satisfied. However, if the opposite happens, the product performance is below expectations, then consumers will feel very dissatisfied. The research results show that the soft skills competencies of librarians at the FKIP UHAMKA Library are classified in the outstanding category, proven by the average value obtained, which is 3.39. User satisfaction in the FKIP UHAMKA library is also classified in the very high category, as evidenced by the average value obtained, which is 3.50. Between these two variables, a correlation is seen from the significance value of 0.000 <0.05. The correlation level is significant, with a value of 0.814. The direction of the relationship is positive, and the level of relationship vi is extreme, with a correlation coefficient interval value between 0.80 -1.000. The results of simple linear regression analysis calculations are Y = 11,929 + 0.747X, and R Square is 0.663, meaning that the influence of librarian soft skill competency on user satisfaction is 66.3%